Respostas
respondido por:
3
f(x)=x²-9x+8, f(x)=0
x²-9x+8=0
-b±√b²-4ac/2a=
-(-9)±√(-9)²-4.1.8/2.1=
9±√81-32/2=
9±√49/2=
x'=9+7/2=8
x"=9-7=1
substituindo:
f(8)=x²-9x+8
f(8)=8²-9.8+8
f(8)=64-72+8
f(8)=-8+8
f(8)=0
f(1)=x²-9x+8
f(1)=1²-9.1+8
f(1)=1-9+8
f(1)=0
x²-9x+8=0
-b±√b²-4ac/2a=
-(-9)±√(-9)²-4.1.8/2.1=
9±√81-32/2=
9±√49/2=
x'=9+7/2=8
x"=9-7=1
substituindo:
f(8)=x²-9x+8
f(8)=8²-9.8+8
f(8)=64-72+8
f(8)=-8+8
f(8)=0
f(1)=x²-9x+8
f(1)=1²-9.1+8
f(1)=1-9+8
f(1)=0
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás